Wettability Properties of Heat-Treated Oil Palm Trunk Under Various Heating Times. Issue 1 (September 2021) - Murda, Rio Ardiansyah; Maulana, Sena; Mangurai, Silvia Uthari Nuzaverra Mayang; Augustina, Sarah; Bindar, Yazid
Abstract: Oil palm trunk has become one of the waste that could damage the environment. Efforts that could be made to minimize the impact oil palm trunk's existence were to turn the oil palm trunk into composite products. A composite product that could be made from palm oil trunks was blockboard. Oil palm trunk could be used as cores on block boards. Oil palm stems as raw material still have weaknesses. This weakness was the low dimensional stability due to hygroscopic properties. The treatment that could be done to increase dimensional stability while improving the adhesive quality was heat treatment. In this study, heat treatment of 140 °C and 160 °C for 1, 2, and 3 hours was carried out. The obtained results were 116.10°, 128.44°, and 133.52° for 1, 2, and 3 hours of treatment sequentially. The L* value in the heat-treated OPT tended to decrease, while the a* and b* values tended to increase compared to the control. The brightness level (L*) of the heat-treated OPT was more affected by temperature than the heat treatment time. Meanwhile, the a* and b* values were almost identical between treatments but differed from the controls. The total color change (?E) of the heat-treated OPT was not too large between treatments (moderate dark orange), but differed from the control (mostly desaturated dark orange).